Serum angiopoietin-related growth factor (AGF) levels are elevated in gestational diabetes mellitus and associated with insulin resistance - Boztosun, Abdullah; Koksal, Deveci; Remzi, Atilgan; Fatih, Kilich; Sinem, Soylemez Melike (Via Medica, 2012)
Objective: Angiopoietin-related growth factor (AGF) is associated with angiogenesis but it can also affect glucose and energy metabolism. The aim of the study was to determine AGF levels in gestational diabetes mellitus (GDM). Materials and Methods: The study included 44 patients with GDM (GDM group) and 33 non-diabetic, healthy women in the third trimester of pregnancy (control group). We analyzed serum levels of AGF and other biochemical and anthropometric markers in all subjects. Results: The study revealed that serum AGF levels were significantly higher in patients with GDM (113.30 +/- 69.92 ng/ml) than in controls (52.30 +/- 35.59 ng/ml), (p-value<0.001). Fasting glucose (117.59 vs. 82.18), homeostasis model of assessment - insulin resistance (HOMA-IR), (2.91 vs. 1.75) diastolic (74.20 vs. 70.00) and mean (89.09 vs. 84.84) blood pressure were found to be significantly higher in the GDM group when compared to the control group (p-value<0.05). There was a significant positive association between AGF and HOMA-IR in the GDM group. Conclusions: Although gestational diabetes mellitus can be a predictor of serum AGF level, further studies are needed to explain the physiologic roles of AGF in glucose metabolism.
Keywords: Angiopoietin-related growth factor; ANGPTL6 protein; human, diabetes; gestational